Netnographic Approach: The Influence Of Social Media On Zakat Awareness Among Young Muslim Generations - Adi Alam; Dyarini Dyarini (Journal of Social Research, 2025)
This study aims to analyze the influence of social media on zakat awareness among the young generation of Muslims using a netnography approach. The development of digital technology has changed the way the younger generation interacts, obtains information, and understands religious values, including the obligation of zakat. Through a netnography approach, this study observes the interactions, conversations, and representation of zakat values on various social media platforms such as Instagram, TikTok, and X (Twitter). Data was collected through online observations, upload documentation, and content analysis related to zakat campaigns, Islamic influencers, and digital amil zakat institutions. The results of the study show that social media plays a significant role in increasing awareness and participation of zakat among the younger generation, especially through visual narratives, personal testimonials, and humanitarian value-based campaigns. However, it was also found that this level of awareness is still emotional engagement and has not completely transformed into behavioral engagement (the behavior of paying zakat regularly). This research emphasizes the importance of authentic, educational, and interactive digital-based zakat communication strategies to strengthen zakat literacy in the social media era.